2018
DOI: 10.1111/dom.13256
|View full text |Cite
|
Sign up to set email alerts
|

A 52‐week extension study of switching from gemigliptin vs sitagliptin to gemigliptin only as add‐on therapy for patients with type 2 diabetes who are inadequately controlled with metformin alone

Abstract: We investigated the long-term efficacy and safety of gemigliptin and the efficacy and safety of gemigliptin treatment after once-daily treatment with sitagliptin 100 mg, in patients with type 2 diabetes. This was a 28-week extension of a 24-week, randomized, double-blind, parallel study of gemigliptin or sitagliptin added to ongoing metformin therapy. After randomization to sitagliptin 100 mg qd (S), gemigliptin 25 mg bid (G1) or gemigliptin 50 mg qd (G2) and after completing 24 weeks of treatment, 118 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The details of the studies included in this meta-analysis are shown in Table 1. The studies that were evaluated but excluded are summarized in Table 2 [15,[20][21][22][23]. The study by Han et al [21] was excluded as it was an open observational extension of an RCT wherein the placebo was replaced with linagliptin.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the studies included in this meta-analysis are shown in Table 1. The studies that were evaluated but excluded are summarized in Table 2 [15,[20][21][22][23]. The study by Han et al [21] was excluded as it was an open observational extension of an RCT wherein the placebo was replaced with linagliptin.…”
Section: Resultsmentioning
confidence: 99%
“…There was no increased risk of adverse effects with gemigliptin compared with sitagliptin [10]. This study was extended by 28 weeks in which patients who had been treated with sitagliptin were switched over to gemigliptin, and so all T2DM subjects received 50 mg gemigliptin daily for 28 weeks [11]. HbA1c reduction from baseline was −1.06 in subjects who continued to receive gemigliptin while an additional 0.1% hba1c reduction from baseline was noted in patients who were switched from sitagliptin to gemigliptin [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested positive effects of DPP‐4 inhibitors, these studies had small sample sizes, and the risks and benefits of DPP‐4 inhibitors in terms of CVD remain unclear 9,10 . Clinical studies have shown that gemigliptin, a novel DPP‐4 inhibitor, has glucose‐lowering efficacy similar to that of sitagliptin or linagliptin 11,12 . However, studies of its effect on cardiovascular safety are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Clinical studies have shown that gemigliptin, a novel DPP-4 inhibitor, has glucose-lowering efficacy similar to that of sitagliptin or linagliptin. 11,12 However, studies of its effect on cardiovascular safety are lacking. Considering the increased risk of hospitalizations in patients with HF reported in some studies of DPP-4 inhibitors, any direct effects of gemigliptin on cardiac function would be clinically important.…”
mentioning
confidence: 99%